Inactivation of Escherichia coli O157:H7 in hamburgers by gamma irradiation - Chirinos,Rodolfo R.O. (2002)
Escherichia coli O157:H7 causes bloody diarrhoea, haemorrhagic colitis and life-threatening complications like haemolytic uremic syndrome and thrombotic thrombocitopenic purpura. Among foods associated with outbreaks caused by this pathogen, hamburger is the most common one. The aim of this research was to determine the radiation dose to reduce the population of E. coli O157:H7 in hamburgers to non-detectable levels in order to render a safer product. Hamburgers, inoculated with Escherichia coli O157:H7, were exposed to gamma radiation (60Co) treatment, with doses ranging from 0 to 0.7 kGy. The average temperature during the process was 5.6ºC. Non-inoculated hamburgers were submitted to sensory evaluation after being exposed to irradiation doses of 0.8 kGy and 1.0 kGy. The D10 for the pathogen varied from 0.17 kGy to O.27 kGy in hamburger. Considering the highest D10 value in hamburger, a dose of 1.08 kGy would be sufficient to reduce E. coli O157:H7 contamination in 4 log cycles, without affecting the sensory attributes of the product.